Sir Cumference and the sword in the cone - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 2003)
Sir Cumference, Radius, and Sir Vertex search for Edgecalibur, the sword that King Arthur has hidden in a geometric solid.
630
Accelerated Reader AR
Keywords: Mathematics -- Juvenile literature; Geometry -- Juvenile literature; Mathematical recreations -- Juvenile literature